The Use and Abuse of the Logical Framework Approach: A Review of Inter national Development NGOs' Experiences - Bakewell, Oliver; Garbutt, Anne (Swedish International Development Cooperation Agency, 2005)
The logical framework approach (LFA) has come to play a central role i n the planning and management of development interventions over the la st twenty years. Although the logical framework has become universally known, it is far from universally liked. It has been the subject of m uch criticism over the years, concerning both the theoretical basis of the approach, and the way it is applied in practice. In this review, we have attempted to take stock of the current views of international development NGOs on the LFA and the ways in which they use it.